O uso de rubricas como instrumento pedagógico no percurso de ensino-aprendizagem e avaliação formativa - Borges, Carla Renata de Souza Teixeira (2023)
The present work aimed to expand the knowledge about using rubrics in the classroom and the formative assessment process. The research focus was pedagogical practice and, from this cut, the need to better understand this instrument and its characteristics emerged. With the theoretical findings mainly in English Language, it was understood the need to expand the reflection promoted by these authors, conducting a literature review. From this study it was possible to deepen the knowledge about the definition, applicability, and production of this instrument for the classroom. In addition, it was possible to better understand its use in the student and teacher evaluation processes and in the teaching and learning process. To broaden the understanding about the advantages of the use of rubrics, it was necessary to establish relationships about the cognitive actions performed by students in the process of metacognition and self-regulation, in addition to establishing the bases of classroom assessment and formative assessment. It was possible to understand that, more than the instrument itself, it is the understanding of pedagogical practice and its perspectives that leads to the formative use of this instrument. At the same time, the understanding of the parameters that constitute the rubric makes it possible to transform teaching practice into a more formative and reflective model, making room mainly for the students' performance in this journey. The classroom can be a place for promotion of actions that make learning a dialogical process, and the rubrics can play an important role in consolidating this perspective